2020
DOI: 10.1111/sltb.12640
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Stigma Toward Nonsuicidal Self‐Injury: An Examination of Implicit and Explicit Attitudes

Abstract: Evidence suggests that individuals without a history of nonsuicidal selfinjury (NSSI) are likely to view NSSI as a stigmatized behavior. However, there is limited evidence evaluating the presence of self-stigma among individuals who have engaged in NSSI. Methods: We recruited a university sample (n = 351) and employed implicit and explicit measures to examine the degree of stigmatization toward those with NSSI scarring, as compared to nonintentional disfigurement (i.e., accidental scarring) and to tattoos (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
(122 reference statements)
0
22
0
Order By: Relevance
“…Previous research has suggested that NSSI influences subsequent stress in romantic and parent-child relationships, and the occurrence of other interpersonal stressful events ( Burke et al, 2015 ; Miller et al, 2018 ). Additionally, engaging in NSSI in and of itself may also be stressful, connected to feelings of shame ( Sheehy et al, 2019 ) and self-stigma ( Piccirillo et al, 2020 ). These possibilities should be explored in future research, in studies on the association between perceived stress and NSSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that NSSI influences subsequent stress in romantic and parent-child relationships, and the occurrence of other interpersonal stressful events ( Burke et al, 2015 ; Miller et al, 2018 ). Additionally, engaging in NSSI in and of itself may also be stressful, connected to feelings of shame ( Sheehy et al, 2019 ) and self-stigma ( Piccirillo et al, 2020 ). These possibilities should be explored in future research, in studies on the association between perceived stress and NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, theories of stress generation suggest that engaging in NSSI could lead to experiencing heightened stressors (e.g., interpersonal disruption) ( Burke et al, 2015 ; March-Llanes et al, 2017 ). Further, engaging in NSSI may decrease an individual’s self-compassion (rather than the reverse), given that NSSI is a highly stigmatized behavior ( Lloyd et al, 2018 ; Piccirillo et al, 2020 ). Experiences of guilt and shame following NSSI are commonly retrospectively reported among adolescents and young adults ( Klonsky & Glenn, 2009 ; Laye-Gindhu & Schonert-Reichl, 2005 ), suggesting that NSSI may not only be impacted by self-compassion, but NSSI may impact one’s self-beliefs as well ( Xavier et al, 2016 ).…”
Section: Study Purposementioning
confidence: 99%
“…Despite this, prior to the onset of the COVID-19 pandemic, approximately half of school-aged adolescents did not seek any support following an incident of self-harm (15), and only 1in-8 presented to health services for medical treatment (16). Common reasons for this included the stigma and self-stigma associated with self-harm (17,18), and a lack of knowledge about where to seek help (15). For those who do seek help, the previously published literature indicates that friends and family members are the most commonly reported sources of support (15).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous online forum content [ 11 ], the current study demonstrated that scar concealment is common. Many individuals hide scars and treat them secretly in private because of social stigma [ 26 ]. However, considering that NSSI can induce serious safety issues by causing infection or secondary disease of wounded parts, in addition to scars formed on the skin, individuals need to understand the importance of adequate wound treatment and inform them about coping methods.…”
Section: Discussionmentioning
confidence: 99%